Adapting to Inflationary Pressures: Household Coping Strategies in Urban Egypt (2016– 2025) - Kamal, Mohamed Mohamed Ashraf (AUC Knowledge Fountain, 2025)
Over the past decade, Egypt has faced persistent economic challenges including repeated currency devaluations, high inflation rates, subsidy reforms such as the gradual reduction of food and energy subsidies, and the ripple effects of global crises that have significantly impacted household well-being, especially in urban areas. These pressures have eroded purchasing power and heightened food insecurity, especially among low- and middle-income families. Although substantial attention has been paid to macroeconomic indicators, there remains a critical gap in understanding how households adapt on a daily basis to manage financial stress and sustain their livelihoods. This inquiry is especially timely, as household resilience plays a central role in social stability and long-term economic development in the face of compounding shocks. This thesis explores how urban households in Egypt have responded to economic hardships by adjusting their consumption patterns and making difficult expenditure decisions. Using a mixed-methods approach, the study combines quantitative analysis from nationally representative survey data with qualitative insights drawn from in-depth interviews with low- and middle-income households. The findings reveal a spectrum of coping strategies, including reducing food quantity and quality, cutting healthcare and education spending, and making lifestyle sacrifices. These strategies vary across income levels, household sizes, and educational backgrounds, with middle-income families often bearing the heaviest burden as mostly excluded from most forms of assistance due to their income level, yet increasingly unable to keep up with the growing financial pressure.